GENDER AND SOCIAL FACTORS AS PREDICTORS FOR THE DEVELOPMENT OF DISORDERS OF THE AUTONOMIC NERVOUS SYSTEM IN VETERANS OF THE ANTI-TERRORIST OPERATION* - O.D. Havlovsky; I.A. Holovanova (Проблеми екології та медицини)
Over the past seven years, an armed conflict has taken place in the eastern part of Ukraine, leading to significant human losses and involving an increased emotional and physical strain on participants (both military and civilian), post-traumatic stress, which has a devastating effect on the mental and somatic sphere of the individual, changes its spiritual values. Measurement of the autonomic nervous system (excitability, irritability, apathy, lethargy; reduced efficiency; insomnia; hyperesthesia, a feeling of "a lump in the throat") was performed in servicemen who were treated at the Poltava Regional Clinical Hospital for War Veterans during 2019-2020. Predictors were social factors (employment and marital status) and the gender of patients. The influence of predictors on the development of disorders of the autonomic nervous system was determined by the method of the odds ratio. As a result of statistical calculations, risk factors for clinical manifestations of disorders of the autonomic nervous system were identified, that unemployment, on the one hand, increases the risk of apathy and reduces efficiency, but on the other - the unemployed have better sleep; in married people, such manifestation as a feeling of "a lump in a throat" is more often observed. Analyzing the influence of sex, it was found that men are more likely to feel aroused, and women are less likely to feel "a lump in the throat".